Public transit of the future: Enhancing well-being through designing human-centered public transportation spaces - Yasaman Hakiminejad; Elizabeth Pantesco; Arash Tavakoli (Transportation Research Interdisciplinary Perspectives)
Studies show that psychological effects are one of the top concerns for public transportation users. While many Americans spend a significant portion of their time in public transportation spaces, the impact of the design and maintenance of these spaces on user well-being has not been fully studied. In this study, we conducted a survey to better understand the effect of implementing different designs on people’s well-being and perceptual metrics (N = 304). Participants were presented with six images depicting different cabin configurations, including (1) the current version of the cabin space, (2) a low-maintenance version, (3) an aesthetically enhanced version, (4) a bike rack-enabled version, (5) a version with an added workspace, and (6) an improved version with biophilic design. After viewing each image, participants’ well-being metrics (e.g., stress, and emotion) and their public transportation perception metrics (e.g., perceptions of safety, and reasonable cost) were evaluated. Our results from linear mixed-effect modeling indicated that adding functional amenities and biophilic design elements led to an overall enhancement in well-being and perceptual metrics. Conversely, low maintenance worsened all measured well-being metrics. This research lays the ground for developing human-centered public transportation spaces that can lead to an increase in public transportation adoption.